Does depression affect the association between prosocial behavior and anxiety? A cross-sectional study of students in China - Zhang, Xiyan; Lv, Tao; Leavey, Gerard; Zhu, Na; Li, Xin; Li, Yan; Chen, Yanhua (Frontiers in Public Health, 2023)
Background: A growing number of studies have suggested that adolescents' prosocial behavior can protect against depression and anxiety. It is known that anxiety and depression are often comorbid. However, it remains unclear if when depression is present, prosocial behavior remains protective against anxiety, and if when anxiety is present, prosocial behavior remains protective against depression.The purpose of this study was to determine the association of anxiety and depressive with prosocial behavior.: A large representative sample of middle-school students was recruited for a cross-sectional study and completed standardized instruments (the Children's Depression Inventory (CDI), Screen for Child Anxiety Related Emotional Disorders-Child version (SCARED-C), and Strengths and Difficulties Questionnaire (SDQ)). We used structural equation modeling (SEM) to examine the protective effect of prosocial behavior against anxiety when depression was present.Results: A survey of 3,510 students was conducted, and the final analysis included 3,169 students, comprising 1,616 boys (51.0%) and 1,553 girls(49.0%), with a mean age of 13.09 years (SD = 1.31, range 11 -16).The prevalence rates of anxiety and depression in early adolescents were 31.6% and 16.7%, respectively.More than two-thirds of depressed adolescents had comorbid anxiety, while more than one-third of anxious adolescents had comorbid depression. Regression models showed that compared with depressed adolescents, adolescents without depressive symptoms exhibited a significant negative correlation between prosocial behaviors and anxiety and depression (β = -0.01, p>0.01，β = -0.06, p>0.01；β = -0.11, p< 0.01，and β = -0.17, p< 0.01). There was no difference in the relationship between prosocial behavior and depression between anxious and non-anxious adolescents (p>0.05).Conclusions: Anxiety and depression are common in adolescence and are often comorbid disorders. However, the comorbidity is not symmetrical. Specifically, the protective effect of prosocial behavior against anxiety is weaker in depressed adolescents. Findings are discussed in light of related research and theory, and insights for intervention programs and future research are presented.